The Influence of Environmental Components on Student Learning Outcomes in Economics Subjects at Banda Aceh City High School - Hidayat, Syarif; Jaya, Alfi Syahril Fuadi; Zulfadhli, Zulfadhli (Jurnal Ragam Pengabdian, 2024)
Environmental factors play a crucial role in the learning process to achieve optimal student learning outcomes. These factors include politics, socio-culture, security, economy, religion, and nature. This study aims to determine the influence of environmental components on student learning outcomes in economics subjects at high schools in Banda Aceh City. A quantitative approach with an explanatory research design was employed. The sample consisted of 60 students selected using stratified random sampling from six high schools. Data were collected through questionnaires and observations, then analyzed using multiple linear regression, coefficient of determination (R²), and hypothesis testing (t-test and F-test). The results indicate that all environmental components partially and simultaneously have a positive and significant influence on student learning outcomes. The political component shows the highest influence, followed by religion, nature, economy, and socio-culture. These findings confirm that a supportive learning environment significantly contributes to improving student academic achievement in economics subjects.